A igreja católica e a ditadura militar na Paraíba: uma história de luta pela defesa dos direitos humanos nos anos da distensão política (1974-1979) - Silva, Janaína Gomes da (2019)
This work deals with the work of the Catholic Church in the state of Paraíba under the leadership of Archbishop José Maria Pires, in the face of the dictatorship established in the country in 1964, by means of a civil-military coup. We have the central aim of researching the period of political distension, which was initiated by the military in 1974, until the year of the enactment of the Amnesty Law, in 1979. Thus, this research places itself in the field of New Political History in its dialogue with Cultural History, and from this perspective, we use the concept of Political Culture to understand that it assists us in understanding social reality, encompassing power relations in articulation with social relations. The sources of research used to carry out this work were: analysis of the main circulation newspapers of the period, such as A União, O Norte and Correio da Paraíba; the Dossier of the Military Regime that is in the Archive of the Archdiocese of Paraíba; the documentation originating from the National Information Service (SNI) and the Truth Commission of Paraíba, in addition to a comprehensive bibliographical review of the period. It should be added that this text is divided into three chapters that seek to elucidate the following themes: The process of political opening of the Military Regime; The work of the Archdiocese of Paraíba, led by Archbishop José Maria Pires, and finally, a discussion on cases of human rights violations in this historical context of "slow, gradual and safe opening."